People, peace, and power : conflict transformation in action - Francis, Diana (Pluto Press, 2002)
"Millions of people around the world live in countries torn apart by war, where violence and suffering are part of everyday life. Yet in all those countries there are groups of people working for peace in the midst of war, standing up for human rights and decency. What difference can they make? What can be done to support them, and to help dialogue to happen in the midst of hostility and violence?" "This book examines these questions, focusing on the roles that ordinary people can play as peace builders in societies where violence and antagonism have become the norm, where inter-communal relationships are fractured or where institutions and the rule of law have collapsed. It examines the theory and practice of conflict transformation and its relevance for different cultures and contexts. Using extensive case studies taken from practical workshops - the most frequently used form of conflict intervention - in the Balkans and around the world, it shows both the power and the complexity of such encounters."--Jacket.